2023
DOI: 10.3390/horticulturae9111178
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Mechanisms Underlying Defense Responses of Horticultural Crops to Botrytis cinerea

Rui Li,
Yulin Cheng

Abstract: Horticultural crops are a crucial component of agriculture worldwide and have great economic value. The notorious plant fungal pathogen Botrytis cinerea can cause gray mold disease in over 200 horticultural crops, leading to severe economic losses. Investigating the mechanisms underlying plant defense responses to pathogens is crucial for developing new strategies for effectively controlling plant diseases, and much progress has occurred in the mechanisms underlying defense responses of horticultural crops to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 154 publications
0
1
0
Order By: Relevance
“…In a recent review of the mechanisms underlying plant defence responses to B. cinerea , Li and Cheng [ 525 ], identified transcriptional regulation and hormone transduction pathways as key aspects of plant immunity to counteract the pathogen. The authors identified specific proteins, hoping for advances in selection for resistance in the host as well as the use of elicitors and microorganisms.…”
Section: Perspectivesmentioning
confidence: 99%
“…In a recent review of the mechanisms underlying plant defence responses to B. cinerea , Li and Cheng [ 525 ], identified transcriptional regulation and hormone transduction pathways as key aspects of plant immunity to counteract the pathogen. The authors identified specific proteins, hoping for advances in selection for resistance in the host as well as the use of elicitors and microorganisms.…”
Section: Perspectivesmentioning
confidence: 99%